Attractiveness of various protein sources to juvenile rockfish (Sebastes schlegeli, Hilgendorf 1880). Issue 3 (2nd July 2020) - Kim, Hee Sung; Baek, Seong Il; Lee, Ki Wook; Jeong, Hae Seung; Cho, Sung Hwoan
ABSTRACT: The attractiveness of various protein sources of 16 feed ingredients was determined in juvenile rockfish ( Sebastes schlegeli ) by using reinforced acrylic tank composed of three equally divided rectangular attracting chambers and an acclimatization chamber. Thirty fish were held in the acclimatization chamber at a time and tournament comparison of feed ingredients was applied to evaluate attractiveness. Jack mackerel (JM) (40.0%), sardine (SM) (33.3%), Pollack (PM) (40.0%), shrimp (SHM) (36.7%), mussel meal (40.0%) and oyster (43.3%) meals achieved the highest feeding attractiveness to rockfish in the 1 st through 6 th preliminary test, respectively. JM (40.0%), SHM (36.7%), squid meal (SQM) (33.3%), SM (40.3%), PM (40.0%) and PM (36.7%) achieved the highest feeding attractiveness to fish in the 7 th through 12 th preliminary test, respectively. Among the top five feed ingredients showing high attractiveness to rockfish, JM achieved higher attractiveness than PM and SHM in the 1 st trial. In the 2 nd trial, attractiveness of JM to rockfish was higher than SM and SQM. SM achieved higher attractiveness to rockfish than SQM, but not different from PM throughout the 30-min observation in the 3 rd trial. The strongest feeding attractant response of rockfish was observed in JM, followed by SM, SQM, PM, and SHM, in order among various feed ingredients.